Association Between Physical Activity, Sedentary Behavior and Sleep Disorders in Chronic Obstructive Pulmonary Disease Patients: A Cross-Sectional Study - Ma X; Zhang Q; Gao X; Sun M (International Journal of COPD)
Xianghui Ma,1 Qing Zhang,2 Xigang Gao,3 Mingxiang Sun4 1Department of Rheumatology, Dongying City People’s Hospital, Dongying, Shandong Province, 257091, People’s Republic of China; 2Department of Call Back Center, Fifth People’s Hospital of Dongying, Dongying, Shandong Province, 257000, People’s Republic of China; 3Boxing County Hospital of Traditional Chinese Medicine, Binzhou, Shandong Province, 256500, People’s Republic of China; 4Department of Respiratory and Critical Care Medicine, Dongying City People’s Hospital, Dongying, Shandong Province, 257091, People’s Republic of ChinaCorrespondence: Mingxiang Sun, Department of Respiratory and Critical Care Medicine, Dongying City People’s Hospital, No. 317, Nanyi Road, Dongying, Shandong Province, 257091, People’s Republic of China, Email xiangzi78@126.comObjective: Sleep disorder is a common comorbidity in chronic obstructive pulmonary disease (COPD). We aim to explore the potential association between daily sitting time (DST), leisure-time physical activity (LTPA) and sleep disorders in COPD patients.Methods: The sleep, LTPA, and DST data of participants with COPD were extracted from the National Health and Nutrition Examination Survey (NHANES) portal (2007– 2012), basing on Global Physical Activity Questionnaire. The t-test, Mann–Whitney test, or chi-square test were employed to analyze the differences between two groups. The weighted binomial logistic regression model was used to estimate the odds ratio (OR) and 95% confidence interval (CI) of DST and LTPA on sleep disorders. The analyses were conducted from April 1 to July 1, 2023.Results: A total of 2063 COPD samples were included in this work, of which 58% had LTPA < 150 min/wk and 48% had DST > 6h. Patients with sleep disorders had longer sedentary time (DST > 6h: 151, DST > 8h: 105) and less physical activity (LTPA < 150min/wk: 185). Longer sedentary time was correlated with a higher risk of sleep disorders, while LTPA showed no significant correlation with sleep disorders. The conjoint analysis revealed that the risk of sleep disorders in patients with LTPA < 150 min/wk and DST > 8h was 5.88 times (95% CI: 1.80– 19.2) great than that of patients with LTPA≥ 150 min/wk and DST < 4h.Conclusion: COPD patients often lacked physical activity and exhibited sedentary behaviors. Long-term sedentary behavior was associated with elevated risk of sleep disorders in COPD patients. More light intensity physical activity and supervised exercise programs are probably good choices to prevent sleep disorders in COPD population.Keywords: chronic obstructive pulmonary disease, COPD, sleep disorders, physical activity, sedentary behavior, National Health and Nutrition Examination Survey, NHANES